Supplemental Material: Detrital zircons from Late Paleozoic Ice Age sequences in Victoria Land (Antarctica): New constraints on the glaciation of southern Gondwana - Luca Zurli (10332290); Gianluca Cornamusini (10332293) (2021)
Raw laser ablation–inductively coupled plasma–mass spectrometry (LA-ICP-MS) analysis and detrital zircon grain shape characterization of the late Paleozoic diamictite samples from Victoria Land, Antarctica.